Fouling and in-situ cleaning of ion-exchange membranes during the electrodialysis of fresh acid and sweet whey. (April 2019) - Talebi, Sahar; Chen, George Q.; Freeman, Benny; Suarez, Francisco; Freckleton, Adrian; Bathurst, Karren; Kentish, Sandra E.
Abstract: This work investigated the fouling of ion-exchange membranes during the electrodialysis of sweet and acid dairy whey. Fresh whey was used, rather than solutions made up in the laboratory, giving a unique perspective. While membrane fouling occurred in all experiments, the effects on system performance were limited. Reductions in the current during pure NaCl circulation fell to a minimum of 80% of the original value after 5 h of whey processing. The use of an alkaline concentrate resulted in the strongest increase in system resistance, but the mineral deposits formed appeared to detach readily, thereby reducing these effects. The use of an acidic concentrate gave significantly greater rates of lactic acid removal, which is important in industrial applications. A solution of HCl with a pH of 1.0 ± 0.15 was effective for in-situ cleaning of the mineral deposits. However, protein deposits were not readily removed using the recommended base cleaning formula of 3% NaCl at a pH of 9.2 ± 0.2. Highlights: Fouling during electrodialysis under different concentrate pH is studied. Protein fouling was similar for both types of whey under acidic concentrate pH. Greater removal of lactate ions was observed with an acidic concentrate. Mineral scaling was minimised by adjustment of concentrate conductivity. In-situ acid cleaning using HCl was effective for removing mineral deposits.